Concordance of Biochip-Based and LC-MS/MS Methods in Urine and Blood Samples in Screening for Amphetamine and Methamphetamine - Murat Akbaba; Aysun Baransel Isir (Diagnostics, 2025)
Objectives: This study aimed to evaluate the efficacy and reliability of LC-MS/MS and biochip-based screening in detecting narcotics from blood and urine samples. Materials and Methods: In this single-center study, a total of 250 subjects provided urine and/or blood samples: 234 provided urine and blood samples, and 16 provided only blood samples. Biochip-based narcotics screening was performed on 234 urine and 16 blood samples, and all samples were analyzed using tandem liquid chromatography-mass spectrometry (LC-MS/MS). Results: The two most prevalent narcotics were methamphetamine and amphetamine, with both biochip-based array and LC-MS/MS. Cohen’s kappa correlation indicated a substantial agreement between LC-MS/MS and biochip-based screening for both methamphetamine (κ = 0.661, p <0.001) and amphetamine (κ = 0.663, p < 0.001). LC-MS/MS demonstrated near-perfect agreement between urine and blood samples for both methamphetamine (κ = 0.855, p <0.001) and amphetamine (κ = 0.881, p < 0.001). Conclusions: Biochip-based arrays are a valid method offering a faster, less material-intensive alternative to LC-MS/MS for substance detection in forensic examination.